Razrabotka metodologii individual'noi sportivno-tekhnicheskoi podgotovki v dzyudo - Eganov, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to elaborate the methodology of individual technical preparedness' correction in judo wrestling. The offered methodology of jodoka's activities correction was experimentally proved with a help of the pedagogical experiment. It was successfully used in the local teams of the Chelyabinsk district and national teams of Russia. The suggested approaches to the individual corection of the judokas' tactic-technique mastery are possible to be used in some other types of sport.